Analysis of frequency changes in CD8+ regulatory T cell subsets in peripheral blood of individuals with type 1 diabetes - Shu Chen; Gaoqiang Meng; Xing Wang; Hemin Jiang; Min Shen; Xueqin Wang; Chunhua Wang (Diabetology & Metabolic Syndrome)
Abstract Background This study aims to examine the alterations and clinical significance of CD8+ regulatory T cell subsets in the peripheral blood of individuals with type 1 diabetes mellitus (T1DM). Methods From January 2020 to December 2023, a study was conducted involving 40 individuals with T1DM, who visited the Department of Endocrinology at the First Affiliated Hospital of Nanjing Medical University (T1DM group). For comparison, 40 healthy individuals who underwent routine physical examinations at the same hospital during this period were selected as the control group. Peripheral blood mononuclear cells were isolated, and CD8+ T cells were labeled with CD3, CD25 and FoxP3 to analyze their subset frequencies using flow cytometry. The study examined differences in subset frequencies between the two groups and explored correlations between subset frequency, disease duration, and age of onset. Results The frequencies of CD8+ CD25+, CD8+ FoxP3+, CD8+ CD25+ CD3+ and CD8+ FoxP3+ CD3+ subsets in peripheral blood mononuclear cells did not significantly differ between the healthy control group and the T1DM group (P > 0.05). In the T1DM group, the expression level of CD25 on CD8+ T cells showed no correlation with the age of onset or disease duration, and FoxP3 levels were also unrelated to the age of onset, with no statistical differences (P > 0.05). However, within the T1DM group, FoxP3 levels progressively decreased with longer disease duration, demonstrating a statistically significant negative correlation (Pearson r = -0.331, P < 0.05). In the T1DM group, the level of CD3+ CD8+ T cells expressed CD25, and there was no correlation between Foxp 3 level and age of onset, not statistically significant (P > 0.05), but the level of Foxp 3 in the T1DM group decreased with the duration of the disease, (Pearson r= − 0.363, P < 0.05). Conclusion The levels of CD8+FoxP3+ regulatory T cells in peripheral blood mononuclear cells of patients with T1DM show a significant correlation with disease duration, suggesting that these cells may play a critical role in the progression of T1DM.